The world described, or A new and correct sett of maps [Material cartográfico]: shewing the kingdoms and states in all the known parts of the earth with the principal cities and most considerable towns in the world wherein the errors of the ancient geographers are corrected according to the latest observations of travellers as communicated to the Royal Society of London and the Royal Society of Paris - Moll, Herman, m. 1732; Bowles, John; Royal Society (Gran Bretaña) (these maps being the most correct, entertaining, and historical, of any yet made, are sold either single or in setts by John Bowles, Print and Map-seller, at the Black Horse in Cornhill, 1708)
Márgenes graduados. - Orientados con rosas con lis. - Meridiando de origen: Londres. - Montes de perfil. - Red hidrográfica. - Costas sombreadas.- Rumbos. - Abundante toponimia. Los mapas están fechados entre 1708 y 1720. Mapas a doble plana con verso de las hojas en blanco Títulos en cartelas decoradas, rodeadas de personajes alusivos a las zonas representadas Contiene: 1. A new and correct map of the world, laid down according to the newest discoveries, and from the most exact observations (1709) -- 2. A New & correct map of the whole world Shewing ye situation of its principal parts. viz the Ooeans, kingdoms, rivers, capes, ports, mountains, woods, trade-winds, monsoons, variation of ye compass, climats, &c. with the most remarkable tracks of the bold attempts which have been made to find out the North East and North West passages (1719) -- 3. To her most sacred Majesty Carolina Queen of Great Britain France & Ireland this map of Europe according to the newest exact observations is most humbly (1708) -- 4. To the Right Honourable William Lord Cowper, Lord High Chancellor of Great Britain, This map of Asia According to the Newest and most Exact Observations is most Humbly dedicated by your Lordship's most Obedient Servant Herman Moll Geographer -- 5. A Map of the East-Indies and the Adjacent Countries; with the Settlements, Factories and Territories, explaining what Belongs to England, Spain, France, Holland, Denmark, Portugal &c . -- 6. To the Right Honourable Charles, Earl of Peterborow, and Monmouth, &c. This Map of Africa according to ye newest and most exact observations -- 7. To the Right Honourable John Lord Sommers Baron of Evesham in ye county of Worcester President of Her Majesty's most Honourable Privy Council etc. This Map of North America According to ye Newest and most Exact Observations . -- 8. A new and exact map of the dominions of the King of Great Britain on ye continent of North America, containing Newfoundland, New Scotland, New England, New York, New Jersey, ...